Operator ordering for generally covariant systems - Ferraro, Rafael (2000)
The constriant operators belonging to a generally covariant system are found out within the framework of the BRST formalism. The result embraces quadratic Hamiltonian constraints whose potential can factorized as a never null function times a gauge invariant function. The building of the inner product between physical states is analyzed for systems featuring either intrinsic or extrinsic time.